1996
DOI: 10.1152/ajplung.1996.270.5.l782
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vasodilator responses to adrenomedullin are reduced by NOS inhibitors in rats but not in cats

Abstract: Responses to and the mechanism of action of adrenomedullin (ADM), the carboxy-terminal fragments of ADM, and calcitonin gene-related peptide (CGRP), a structurally related peptide, were investigated in the pulmonary vascular bed of the rat. Under conditions of elevated tone and controlled pulmonary blood flow in the isolated blood-perfused rat lung, injections of ADM, the 15-52 amino acid carboxy-terminal ADM analogue (ADM15-52), and CGRP caused dose-related decreases in pulmonary arterial perfusion pressure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 0 publications
4
66
1
Order By: Relevance
“…This complete prevention of the vasodilator response, in comparison with the partial prevention reported in other studies, may reflect a more complete inhibition of NOS by the 2 h pretreatment with L-NNA given directly into the coronary arteries in our study. Our observation that NOS inhibition prevented the vasodilator action of ADM in the coronary arteries of sheep is consistent with the reports that NOS inhibition blocks the effect of ADM in most, but not all, vascular beds (Feng et al, 1994;Majid et al, 1996;Nossaman et al, 1996). In the present study, ADM (0.5 mg kg À1 h À1 ) infused i.c., but not i.v., caused a small increase in HR, suggesting that ADM has a direct chronotropic action.…”
Section: R De Matteo and Cn Maysupporting
confidence: 93%
See 1 more Smart Citation
“…This complete prevention of the vasodilator response, in comparison with the partial prevention reported in other studies, may reflect a more complete inhibition of NOS by the 2 h pretreatment with L-NNA given directly into the coronary arteries in our study. Our observation that NOS inhibition prevented the vasodilator action of ADM in the coronary arteries of sheep is consistent with the reports that NOS inhibition blocks the effect of ADM in most, but not all, vascular beds (Feng et al, 1994;Majid et al, 1996;Nossaman et al, 1996). In the present study, ADM (0.5 mg kg À1 h À1 ) infused i.c., but not i.v., caused a small increase in HR, suggesting that ADM has a direct chronotropic action.…”
Section: R De Matteo and Cn Maysupporting
confidence: 93%
“…It has been proposed that the vasodilator action of ADM is mediated by a number of mechanisms, including a direct action on vascular smooth muscle cells via cAMP and Ca 2 ĂŸ mobilisation (Ishizaka et al, 1994;Shimekake et al, 1995), and by stimulation of nitric oxide (NO). Inhibition of nitric oxide synthase (NOS) has been shown to prevent the vasodilator action of ADM in dog kidney (Majid et al, 1996), rat hindquarters (Feng et al, 1994) and in the pulmonary circulation of the rat but not the cat (Nossaman et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] The vasodilatory effect is mediated by cAMP-dependent and nitric oxide-dependent mechanisms. 28,29 Endogenous AM production is enhanced in a variety of cardiovascular diseases through a compensatory mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…For example, pulmonary vasodilator responses were reduced by N-nitro-L-arginine methyl ester (L-NAME) in rats, but not in cats. 27 Currently, there is little data available on the vasodilator effect on veins, whereas Barder et al reported that vasodilatation of femoral veins in canines was endotheliumdependent, but independent of cAMP and cGMP. 28 Thus, the mechanism by which AM achieves direct vasodilatation appears to differ depending on species, the size of blood vessels, or regions where the vessels are isolated.…”
Section: Vasodilator Action Of Ammentioning
confidence: 99%